Acetate as substrate for l-malic acid production with Aspergillus oryzae DSM 1863 - Aline Kövilein; Julia Umpfenbach; Katrin Ochsenreither (Biotechnology for Biofuels, 2021)
Abstract Background Microbial malic acid production is currently not able to compete economically with well-established chemical processes using fossil resources. The utilization of inexpensive biomass-based substrates containing acetate could decrease production costs and promote the development of microbial processes. Acetate is a by-product in lignocellulosic hydrolysates and fast pyrolysis products or can be synthesized by acetogens during syngas fermentation. For the fermentation of these substrates, a robust microorganism with a high tolerance for biomass-derived inhibitors is required. Aspergillus oryzae is a suitable candidate due to its high tolerance and broad substrate spectrum. To pave the path towards microbial malic acid production, the potential of acetate as a carbon source for A. oryzae is evaluated in this study. Results A broad acetate concentration range was tested both for growth and malic acid production with A. oryzae. Dry biomass concentration was highest for acetic acid concentrations of 40–55 g/L reaching values of about 1.1 g/L within 48 h. Morphological changes were observed depending on the acetate concentration, yielding a pellet-like morphology with low and a filamentous structure with high substrate concentrations. For malic acid production, 45 g/L acetic acid was ideal, resulting in a product concentration of 8.44 ± 0.42 g/L after 192 h. The addition of 5–15 g/L glucose to acetate medium proved beneficial by lowering the time point of maximum productivity and increasing malic acid yield. The side product spectrum of cultures with acetate, glucose, and cultures containing both substrates was compared, showing differences especially in the amount of oxalic, succinic, and citric acid produced. Furthermore, the presence of CaCO3, a pH regulator used for malate production with glucose, was found to be crucial also for malic acid production with acetate. Conclusions This study evaluates relevant aspects of malic acid production with A. oryzae using acetate as carbon source and demonstrates that it is a suitable substrate for biomass formation and acid synthesis. The insights provided here will be useful to further microbial malic acid production using renewable substrates.